2020
DOI: 10.47102/annals-acadmedsg.2020364
|View full text |Cite
|
Sign up to set email alerts
|

Interventional Pulmonology and COVID-19: Experience from a Malaysian Tertiary Hospital

Abstract: The ongoing pandemic of COVID-19 has presented multiple challenges to global healthcare services, dictating changes in almost every aspect of daily medical practice. Performing aerosol generating procedures (AGPs) in the field of interventional pulmonology can lead to profound formation of aerosols, leading to a high risk of infection among healthcare workers (HCWs). We share our experiences on performing AGPs in the midst of a COVID-19 pandemic by focusing on changes in AGP practices. In a pandemic, HCWs ough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…A commentary from the respiratory team at a tertiary hospital in Malaysia found that the number of procedures they were carrying out had significantly fallen. They postulated this may be due to reduced movement due to their interstate travel restrictions, avoidance of healthcare services from patients and seeking alternative measures to obtain diagnoses to avoid spread ( 22 ). They also reported anxiety amongst the staff initially regarding the potential spread during AGPs; they found with formal guidelines and information regarding donning/doffing and social distancing eased some concerns.…”
Section: Discussionmentioning
confidence: 99%
“…A commentary from the respiratory team at a tertiary hospital in Malaysia found that the number of procedures they were carrying out had significantly fallen. They postulated this may be due to reduced movement due to their interstate travel restrictions, avoidance of healthcare services from patients and seeking alternative measures to obtain diagnoses to avoid spread ( 22 ). They also reported anxiety amongst the staff initially regarding the potential spread during AGPs; they found with formal guidelines and information regarding donning/doffing and social distancing eased some concerns.…”
Section: Discussionmentioning
confidence: 99%